Formas no personales del verbo en el español medieval - Pawlik, Janusz (Studia Romanica Posnaniensia, 2010)
In this paper we intend to investigate the three elements of the Spanish verb system, ie. infinitive (cantar), present and past participles (cantando, cantado). We will find out the changes undergone by these grammatical forms and their function during medieval Spanish. This period is considered to be crucial for the formation and the future role played by the impersonal forms of verb.